Peran Ombudsman RI Perwakilan Provinsi Bali Dalam Pengawasan Pelayanan Publik Di Dinas PUPR Kota Denpasar - Agus Suharsono; Selfi Budi Helpiastuti; Luh Gede Dewi Sari Astiti (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2023)
Public services in Indonesia are often in the spotlight in society, especially in maladministration actions carried out by public service providers. Such as an increase in reports of alleged maladministration received by the Ombudsman of the Republic of Indonesia in Bali Province. Where in this report the agency that received the highest report was the Department Public Works Service in Denpasar City. With reports of alleged maladministration from the public, it is felt that there is a need for a role from an institution authorized to supervise public services, such as the Ombudsman Institute of the Republic of Indonesia. The purpose of this study is to conduct an analysis regarding the role of the Indonesian Ombudsman Representative of the Province of Bali in supervising public services at the Department Public Works Service in Denpasar City. This study uses a post-positivism approach with descriptive qualitative analysis. The results obtained are the role of the Indonesian Ombudsman Representative for the Province of Bali which is divided into 2 dimensions, namely prevention of maladministration with the sub-dimensional assessment of compliance with public service standards and community participation as well as the report completion dimension with the report completion procedure sub- dimension and the number of completed reports. The Ombudsman of the Republic of Indonesia for the Province of Bali succeeded in carrying out all of these dimensions in the supervision carried out by the Public Works and Public Housing Office of the City of Denpasar